Optimal control model and cost-effectiveness analysis of Maize streak virus pathogen interaction with pest invasion in Maize plant. Issue 1 (1st January 2020) - Alemneh, Haileyesus Tessema; Makinde, Oluwole Daniel; Theuri, David Mwangi
ABSTRACT: In this paper, we proposed and analyzed an optimal control deterministic model for the dynamics of Maize Streak Virus pathogen interaction with a pest invasion on Maize plant to examine the best strategy for maize streak disease elimination. The Pontryagin's maximum principle is applied to derive and study the necessary conditions for optimal control strategies. We obtained the Hamiltonian, the adjoint variables, the characterization of the controls and the optimality system. For minimizing the spread of maize streak disease, three controls namely prevention ( u 1 ), quarantine ( u 2 ) and chemical control ( u 3 ) were incorporated and their impacts were pictorially shown using numerical simulations. We investigated cost-effectiveness using ICER to determine the best strategy. We found that the combination of prevention and quarantine is the best effective strategies in terms of cost as well as health benefits.